Synthesis and photophysical properties of metal complexes of curcumin dyes: Solvatochromism, acidochromism, and photoactivity. (February 2022) - de França, Bruna M.; Oliveira, Simone S.C.; Souza, Lucieri O.P.; Mello, Thaís P.; Santos, André L.S.; Bello Forero, Josué S.
Abstract: Curcumin and its dyes have attracted attention due to their environment-sensitivity and optical properties. However, the free molecule has low photoactivity, which is a limitation for use in photodynamic therapy. To overcome this limitation, we proposed the chelation of a D-π-A-π-D curcumin dye (1) with the metals Cu (II) and Pd (II). The photophysical properties of the curcumin dyes were investigated in different solvents, using UV–vis spectroscopy and time-resolved/steady-state fluorescence techniques. In our results, all curcumin dyes exhibited a positive solvatochromism from non-polar to polar solvents, with the Stokes' shift in the range of 1895–4970 cm −1 . The acidochromism studies were performed in chloroform solution and TLC plates using trifluoroacetic acid (TFA). The results exhibited a negative acidochromism and fluorescence quenching upon gradual addition of TFA, demonstrating reversibility upon addition of triethylamine (TEA). The main mechanism which influences the solvatochromism/acidochromism is the ICT system and fluorescence lifetime decays exhibited mono-exponential fit for aprotic solvents and bi-exponential fit for protic solvents (EtOH and MeOH). Compared to the curcumin ligand (1), the metal complexes (1a-b) exhibited higher singlet oxygen quantum yields (ΦΔ  = 0.36 and 0.54, respectively). The in vitro antimicrobial photoactivity of the compounds was evaluated against six different microorganisms. The results showed that the metal complexes (1a-b) exhibited both antileishmanial (MIC = 2.29 μM against Leishmania amazonensis promastigotes) and antifungal (IC50  = 10 μM against Sporothrix brasiliensis yeasts) activities, while the ligand showed no activity, suggesting the chelation with the metals Cu (II) and Pd (II) may improve its photoactivity. Graphical abstract: Image 1 Highlights: Metal complexes of curcumin dyes were synthesized and their photophysical properties were investigated. The positive solvatochromism was observed from non-polar to polar solvents (1895–4970 cm −1 ). The negative acidochromism and the fluorescence quenching were observed upon gradual addition of TFA. Fluorescence lifetime decays exhibited bi-exponential fit for protic solvents (EtOH and MeOH). Metal complexes of curcumin dyes showed photoactivity against L . amazonensis and S . brasiliensis.